The Influence Of Perceptions And The Level Of Readiness Of Micro, Small And Medium Enterprises (UMKM) On The Implementation Of Sak Emkm In UMKM In Sako Sub-District, Palembang City - Yani, Putri Angga; Dini, Maya; Ikraam, Ikraam (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This study aims to examine the extent to which the perception and readiness of MSME (Micro, Small, and Medium Enterprises) actors influence the implementation of SAK EMKM (Financial Accounting Standards for Micro, Small, and Medium Entities). The focus of this research is on MSME actors in Sako District, Palembang City. The data used in this study are primary data collected directly from respondents through questionnaires. The sample size consists of 320 respondents, determined using the Isaac and Michael table with a probability sampling approach. This quantitative research method is used to test hypotheses based on the data collected. Data analysis was conducted both partially and simultaneously. The results of the multiple linear regression test show that the variables of MSME Actors' Perception (X1) and Readiness Level (X2) have a positive influence on the Implementation of SAK EMKM (Y).